Usefulness of the ultrastructural and immunohistochemical analysis of cardiac biopsy in affected heart - Fidziańska, Anna; Glinka-Lindner, Zofia; Religa, Grzegorz; Walczak, Ewa (Folia Neuropathologica, 2010)
In the last few years endomyocardial biopsy becomes a useful diagnostic tool for the investigation of idiopathic dilated cardiomyopathy. The aim of our current study was to try to identify ultrastructural and immunohistochemical specificity of truncated cardiac proteins in affected heart. The focal loss of plasma membrane continuity together with the lack of dystrophin activity in affected myocytes facilitated to find mutation in dystrophin gene. The accumulation of granulofilamentous desmin-positive material in cytoplasm of myocytes was the main indicator of presented mutation in the desmin gene. Nuclear structure remodeling, concomitantly with loss of lamin A/C activity, contributed to identify mutation in lamin A/C gene. Analysis of hypertrophic heart with disarray of sarcomeres and lack of I-Z-I bands suggested embryonic faiulure in titin activity. All this findings indicate that endomyocardial biopsy reperesent a useful method for a correct diagnosis of heart dysfunction.